Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How to decompose equations below and then solve

1)$$ 2x^3 + 7x - 4 \equiv 0 \pmod{25} $$

2)$$ x^2+4x+2 \equiv 0 \pmod{49}$$

Thank you.

share|cite|improve this question
Are you asking if those equations factor mod n? Do you know about finite fields? – Zach L. Dec 4 '12 at 12:48
I want to get roots and i don't know anything about finite fields? – misi10 Dec 4 '12 at 13:02
Do keep in mind that neither $25$ nor $49$ is a prime, so the product of two non-zero things can be zero in those rings. Another thing is that there is always "completing the square" trick, so the latter polynomial $$x^2+4x+2=x^2+4x+4−2=(x+2)^2−2\equiv(x+2)^2−100 \pmod{49}$$ can be written as a difference of two squares and hence factored. With the first polynomial I would just brute force find its zeros modulo $5$, and then check whether these come from roots modulo $25$. Remember that if $a$ is a root modulo $25$, then it's also a root modulo $5$. – Jyrki Lahtonen Dec 4 '12 at 13:25
If a is a root of modulo 5 then is's also a root module 5? can you explain more 1) ? – misi10 Dec 4 '12 at 13:39
Following @JyrkiLahtonen's hint: $\,a^2-b^2=(a-b)(a+b)\,$ , which is true modulo any natural... – DonAntonio Dec 4 '12 at 13:42
up vote 0 down vote accepted

Completing the square $\rm\ mod\ 49\!:\ x^2\!+4x+2 = (x+2)^2\!-2 \equiv (x+2)^2\! - 10^2 \equiv (x-8)(x+12).\:$ Therefore $\rm\: 7^2\mid (x-8)(x+12)\:\Rightarrow\: 7^2\mid x-8\ $ or $\rm\ 7^2\mid x+12\ $ or $\rm\ 7\mid x-8,\, x+12.\:$ The last case is impossible since it implies that $\rm\:mod\ 7\!:\,\ 8\equiv x\equiv -12.$

Quite likely, the first problem is a misprint for $\rm\:f = 2x^\color{#C00}2+7x-4.\:$ Using the AC method, with $\rm\: X = 2x,\:$ we have $\rm\:2f = X^2+7X-8 = (X+8)(X-1) = (2x+8)(2x-1),\:$ therefore $\rm\: f = (x+4)(2x-1).\:$ Now, as above, apply a case analysis to $\rm\ 5^2\!\mid (x+4)(2x-1).$

share|cite|improve this answer
How to get more example with (modular arithmetic) and (equation)? – misi10 Dec 4 '12 at 19:29

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.